L’assentificazione dell’oggetto e la presentificazione del soggetto nelle opere teatrali di Sarah Kane (Itinera, 2014)
Art as an organization of the empty is a theory that shows a deep affinity to the psychoanalytical processes suggested by Sigmund Freud and Jacques Lacan. Indeed, the artistic experience cannot avoid the vacuum limit or circumscribe it. Art does not omit nor does it fill the need, or absence of this need, though it could outline and border it. The works written by the British playwright Sarah Kane, a spokesperson for the experiential theatre dominated by an aesthetic limit and excess, demonstrate the theory that there is nothing impossible to represent on stage. In fact a symbolic treatment of the real in which the inability to represent the Thing (according to the Lacanian definition) becomes the same condition of a possible representation. The assentification of the object is closely correlated to a subject's presentification. In her works Sarah Kane, expresses the notion of a collision such as a Stoss, named by Heidegger in The Origin of the Work of Art, in which the aesthetic experience together with anguish and death, is aimed at keeping alive the sense of disorientation which is a constituent factor and provisional of being in the world, Daseing.